Effects of the Mean Amplitude of Glycemic Excursions and Vascular Endothelial Dysfunction on Cardiovascular Events in Nondiabetic Patients With Coronary Artery Disease. Issue 5 (26th April 2017) - Akasaka, Tomonori; Sueta, Daisuke; Tabata, Noriaki; Takashio, Seiji; Yamamoto, Eiichiro; Izumiya, Yasuhiro; Tsujita, Kenichi; Kojima, Sunao; Kaikita, Koichi; Matsui, Kunihiko; Hokimoto, Seiji
Abstract : Background: Mean amplitude of glycemic excursion (MAGE) is commonly used to gauge the degree of glucose level fluctuations. MAGE plays a significant role in vascular endothelial dysfunction and cardiovascular events in patients with diabetes mellitus (DM), but its significance is not clear in non‐DM patients. Thus, we examined the impact of MAGE and vascular endothelial dysfunction on clinical outcomes in non‐DM patients with coronary artery disease. Methods and Results: We followed non‐DM patients (n=65) for 12 months who underwent percutaneous coronary intervention and assessed the relationship among MAGE, reactive hyperemia index (RHI) measured by reactive hyperemia peripheral arterial tonometry as endothelial function, and cardiovascular events. Cardiovascular events analyzed were cardiovascular death, myocardial infarction, unstable angina, and revascularizations. Compared with patients with MAGE <65 mg/dL (normal glycemic excursions), the group with MAGE ≥65 mg/dL (high glycemic excursions) had significantly higher high‐sensitivity C‐reactive protein (0.10±0.11 mg/dL versus 0.18±0.13 mg/dL, P =0.006) and lower RHI (0.64±0.21 versus 0.51±0.22, P =0.035). The multivariable analysis identified high MAGE and low RHI (≤0.56) as risk factors associated with cardiovascular events (hazard ratio, 5.6; 95% RI, 1.72–18.4 [ P =0.004] versus hazard ratio, 4.5; 95% RI, 1.37–14.9 [ P =0.013]). When the prognosis was classified by combination with MAGE and RHI, the incidence of cardiovascular events was 46.7% (high MAGE+low RHI), 26.7% (high MAGE+high RHI), 20.0% (low MAGE+low RHI), and 6.6% (low MAGE+high RHI) in descending order ( P =0.014). Receiver operating characteristic curve analysis revealed that MAGE, RHI, and MAGE+RHI were each associated with cardiovascular events (area under the curve 0.780, 0.727, and 0.796, respectively). Conclusions: MAGE was associated with cardiovascular events in non‐DM patients with coronary artery disease. Furthermore, the combination with MAGE and RHI was useful for further subdivision of the risk of cardiovascular events.